Testing scalar versus vector dark matter - Azevedo, Duarte (2022)
We investigate and compare two simple models of dark matter (DM): a vector and a scalar DM model. Both models require the presence of two physical Higgs bosons h1 and h2 which come from mixed components of the standard Higgs doublet H and a complex singlet S. In the vector model, the extra Uð1Þ symmetry is spontaneously broken by the vacuum of the complex field S. This leads to a massive gauge boson Xμ that is a DM candidate stabilized by the dark charge conjugation symmetry S → S , Xμ → −Xμ. On the other hand, in the scalar model the gauge group remains the standard one. The DM field A is the imaginary component of S and the stabilizing symmetry is also the dark charge conjugation S → S (A → −A). In this case, in order to avoid spontaneous breaking, the Uð1Þ symmetry is broken explicitly, but softly, in the scalar potential. The possibility to disentangle the two models has been investigated. We have analyzed collider, cosmological, DM direct and indirect detection constraints and shown that there are regions in the space spanned by the mass of the nonstandard Higgs boson and the mass of the DM particle where the experimental bounds exclude one of the models. We have also considered possibility to disentangle the models at eþe− collider and concluded that the process eþe− → Z þ DM provides a useful tool to distinguish the models.